USING ‘MIME GAME’ TO TEACH VOCABULARY TO YOUNG LEARNERS - Mardhatillah Mardhatillah; Ratmanida Ratmanida (Universitas Negeri Padang, 2016)
In this paper, the author discusses the use of 'mime game' in teaching English vocabulary for young learners. To teach young learners, we must first understand their characteristics and needs. The fact is that young learners love to play. Therefore, learning through playing is the most appropriate way to teach them. One of them is to use the game called as